2021
DOI: 10.1093/infdis/jiab490
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Immune Activation and Inflammation in Individuals With Postacute Sequelae of Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Abstract: Background The biological processes associated with postacute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (PASC) are unknown. Methods We measured soluble markers of inflammation in a SARS-CoV-2 recovery cohort at early (<90 days) and late (>90 days) timepoints. We defined PASC as the presence of 1 or more coronavirus disease 2019 (COVID-19)–attributed symptoms beyond 90 day… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
226
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(248 citation statements)
references
References 45 publications
14
226
6
2
Order By: Relevance
“…We log-transformed all biomarkers to reduce influence of outliers and to permit interpretation of fold-changes. As in prior work, 38 we compared the ratio of the mean transformed values for each biomarker between those with and without persistent neurologic symptoms using linear mixed effects models with terms for PASC, time period (early versus late recovery), and their interaction. This approach permits comparison of the values at early and late time points as well as assessment of whether trajectories in marker values differ between those with and without persistent symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We log-transformed all biomarkers to reduce influence of outliers and to permit interpretation of fold-changes. As in prior work, 38 we compared the ratio of the mean transformed values for each biomarker between those with and without persistent neurologic symptoms using linear mixed effects models with terms for PASC, time period (early versus late recovery), and their interaction. This approach permits comparison of the values at early and late time points as well as assessment of whether trajectories in marker values differ between those with and without persistent symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…3237 Recent work has suggested that immune activation might play a role in PASC. 13,38 Inflammatory markers such as interleukin (IL)-6, tumor necrosis factor (TNF)-alpha, and interferon-gamma induced protein (IP)-10 have been associated with ongoing symptoms. 38 These markers, particularly IL-6, may correlate with long-term neuropsychiatric manifestations of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have evaluated persistent inflammation have suggested potential elevations in biomarkers, 116,127 although no clear immunologic pathways have yet to be consistently implicated. We recently demonstrated that during early recovery (i.e.…”
Section: Cov-2 Infection (Pasc)mentioning
confidence: 99%